Diminished biophysical cooling benefits of global forestation under rising atmospheric CO2 - Fei Kan; Hao Xu; Shuchang Tang; Josep Peñuelas; Xu Lian; Caspar T. J. Roebroek; Nazhakaiti Anniwaer; Kai Wang; Shilong Piao (Nature Communications)
Abstract Forestation is a proposed solution for mitigating global warming through carbon sequestration. However, its biophysical effects through surface energy modulation, particularly under rising CO2 levels, is less understood. Here we investigate the biophysical effects of global potential forestation on near-surface air temperature (T a ) under increasing CO2 concentrations using a land-atmosphere coupled model with slab ocean module. Our findings reveal that, under current climate conditions, the biophysical effect of global full-potential forestation can reduce land surface T a by 0.062 °C globally. However, this cooling benefit diminishes as CO2 rises. While elevated CO2 slightly alters evaporative local cooling via stomatal closure and adjustments in forestation-driven rainfall regimes, the dominant reduction stems from non-local mechanisms. Background climate shifts reorganize forestation-induced horizontal temperature advection, weakening remote cooling in the Northern Hemisphere. These findings highlight the necessity of incorporating dynamic forest management strategies to optimize mitigation potential under a changing climate.